Gas‐phase acidity of bis[(perfluoroalkyl)sulfonyl]imides. Effects of the perfluoroalkyl group on the acidity. (23rd May 2014) - Zhang, Min; Sonoda, Takaaki; Mishima, Masaaki; Honda, Tsunetoshi; Leito, Ivo; Koppel, Ilmar A.; Bonrath, Werner; Netscher, Thomas
<x xml:space="preserve">Abstract</x> The gas‐phase acidity (GA) values were determined for a number of perfluoroalkyl‐substituted sulfonylimides by measuring proton‐transfer equilibria using a Fourier transform ion cyclotron resonance (FT‐ICR) mass spectrometer. The GA scale below 286.5 kcal mol−1 for (CF3SO2)2NH was extended and partially revised. The GA value of (C4F9SO2)2NH which is currently the strongest acid was revised from 284.1 to 278.6 kcal mol−1. The effect of fluorine atoms on the acidity of perfluoroalkyl‐substituted sulfonylimides was described with the following model <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghtbz5wt5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />GA=−4.67Nα+0.43Nβ+0.22Nγ+0.18Nδ+314.2</alternatives> where N(α), N(β), N(γ), and N(δ) are the numbers of fluorine atoms at α, β, γ, and δ position in RfSO2 (Rf = perfluoroalkyl group), respectively. This correlation indicates that the electron‐withdrawing ability of the RfSO2 group can be described in terms of the number of fluorine atoms in the perfluoroalkyl group corrected by taking into account their positions. Copyright © 2014 John Wiley & Sons, Ltd.